"Periimplant Mucositis" Secondary to Infection of Residual Bone Allograft Embedded in the Periimplant Sulcus of a Patient With Diabetes: A Case Report. Issue 2 (5th April 2021) - Do, Jonathan H.
Abstract : Introduction: Currently, inflammation of tissue around implants is diagnosed as either periimplant mucositis or periimplantitis, and the etiology is bacterial biofilm colonization of the implant and its transmucosal component. The purpose of this manuscript is to report a case of "periimplant mucositis" secondary to infection of a residual bone allograft embedded in the periimplant sulcus of a patient with diabetes. Case Presentation: A #8 implant was placed and provisionalized in a 46‐year‐old male patient. During implant placement, facial contour augmentation with an allograft (1000‐2000 μm), a collagen membrane, and a connective tissue graft was performed. Healing was uneventful. The crown was removed 9 months after implant placement; a graft particulate was observed in the periimplant sulcus and left undisturbed. The subgingival contour of the crown was adjusted, and the crown was reseated. The patient subsequently developed soreness and foul smell at #8. The crown was removed, and the previously observed graft particulate was more exposed and contaminated. It was removed and the crown was reseated. A month later, symptoms persisted. Palpation produced suppuration. A facial flap was reflected, and residual graft particulates embedded in the facial flap were removed. The site was grafted with a connective tissue graft. Subsequently, symptoms resolved, and the implant was restored. Conclusion(s): Within the limitation of this case report, it appears residual graft materials can get infected once exposed to the oral cavity and subsequently induce an inflammatory response in the surrounding tissue, especially in a patient with hyperglycemia.